Comparison of PMH Between Indonesia and the Netherlands - Sibarani, Clarisa Sondang; Hutagalung, Joshua; Putri, Shabiha Elena; Hutahaean, Triani Cahya; Aliantoni, Yoandhika (International Journal of Social Service and Research, 2025)
This study analyzes the comparison of the Unlawful Acts system between Indonesia and the Netherlands through a qualitative approach with a literature study design. Although both countries share the roots of the same legal system, the development of both shows significant differences in implementation and adaptation to contemporary needs. The Netherlands has developed a broader and more flexible concept through Article 6:162 of the Burgerlijk Wetboek with detailed classification, strict documentation standards, and a mature legal infrastructure. On the other hand, Indonesia still applies the general concept through Article 1365 of the Civil Code without specific classifications and faces challenges in standardizing medical documentation, medicolegal awareness, and implementing digital systems. The fundamental difference can be seen in the philosophical aspects of justice, institutional capacity, proof mechanisms, and adaptation to technological developments. The era of digitalization brings new challenges related to legal accountability in the context of artificial intelligence and digital platforms that require comprehensive regulation. The research found that the Dutch legal system is more responsive to social and technological changes, has a strong transparency mechanism, and an emphasis on communication and patient safety aspects in dispute prevention. Legal harmonization in the context of globalization is an urgent need to facilitate international cooperation. Strategic recommendations include the development of specific classifications, strengthening documentation regulations, developing a legal framework for digital technology, citizen lawsuit reform, and learning from Dutch best practices that can be adapted to the local Indonesian context to improve legal certainty and justice.